Inhibitory Effect of Hydroxymethylfurfural in Viability of BALB/C Mice Splenocytes - Sevda Saleh-Ghadimi; Hamed Jafari-Vayghan; Sorayya Kheirouri; Mohammad Alizadeh (Tabriz University of Medical Sciences, 2019)
Background: This study was designed to discover if hydroxymethylfurfural (HMF) exposure modifies cell proliferation and DNA damage in BALB/c mice splenocytes. Methods: Mitogenesis in T cells and B cells was induced by Concanavalin A (Con A) and lipopolysaccharide (LPS). The colorimetric tetrazolium assay was used to evaluate cell proliferation. DNA damaging consequences were evaluated via measurement of 8-hydroxy-2-deoxyguanosine (8-OHdG) level in BALB/c mice splenocytes. Results: Spleen cells proliferation elicited by ConA, was dramatically suppressed by 25, 50 and 100 mM of HMF. However, there was not any significant difference between various concentrations of HMF. The same result was observed following treatment with LPS and HMF in different concentrations. Eight-OHdG concentration was elevated significantly in HMF treated groups compared with untreated control and mitogens. Conclusion: HMF was found to have immunosuppressing and DNA damaging properties in mM concentrations in mice splenocytes.